Characteristics of schumann resonance as observed in the Indian sector - Sinha, Ashwini K.; Pathan, B.M.; Gurubaran, S.; Selvaraj, C.; Jeeva, K. (My University, 2008)
Schumann Resonances (SR) are lightning generated global electromagnetic modes in extremely low frequency (ELF) range operating in the Earth-ionosphere cavity. The 1st harmonic is at nearly 7.8 Hz and subsequent harmonics are separated by approximately 6 Hz.The phenomena have not been extensively studied in the low and equatorial regions. In this paper an attempt has been made to study the characteristics of SR in the low latitude Indian sectors using ground magnetic data from searchcoil magnetometers operating at Shillong (geographic co-ordinate lat 25034', long 91053', declination=-0.4740). The diurnal pattern of amplitude of a particular harmonic show the dominance of thunderstorm activities in three major sectors viz. south-east Asia, Africa and South America. Sunrise effects are clearly seen as increase in the SR amplitude during local sunrise time. Sunset effect (decrease in SR amplitude during the local sunset time) is also observed in the East-West component, whereas for North-South component is completely masked by the global thunderstorm dominance during that time.
Keywords: Schumann resonance; Extremely low frequency; SR amplitude; ELF wave